Drug synergy as a strategy for compression of morbidity in a Caenorhabditis elegans model of Alzheimer’s disease - Teo, Emelyne (GeroScience, 2020)
Alzheimer’s disease (AD) is the most common cause of dementia worldwide. AD is a multifactorial disease with simultaneous occurrence of several connected pathological processes including mitochondrial dysfunction and impaired proteostasis. Most of these are also implicated in organismal aging per se. The presence of separable pathological conditions poses the opportunity to try combination treatments that target these different processes separately. This approach may provide an effective strategy to target AD; therefore, we investigated whether a combination of metformin (targeting mitochondria and energy metabolism) and lithium (targeting proteostasis) could result in synergistic benefits. In this perspective paper, we looked for benefits in lifespan and healthspan using a transgenic nematode strain, GRU102, which expresses pan-neuronal human amyloid-beta (Aβ). Individually, metformin and lithium extended the lifespan of both non-transgenic GRU101 controls and GRU102. Combination treatment using metformin and lithium did not result in any synergistic increase in GRU102 lifespan, but this treatment did result in a significant compression of morbidity when compared with each individual drug, resulting in relative and absolute extension of healthspan. Despite over-expressing pathogenic human Aβ in their neurons, GRU102 worms treated with the combination treatment enjoyed longer lifespans and significantly compressed morbidity, even compared with untreated non-transgenic animals. These findings suggest combination treatment as a strategy to compress morbidity, and highlight the distinction between healthspan and lifespan. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s11357-020-00169-1) contains supplementary material, which is available to authorized users.